Analytical model for the compressive strength of confined concrete with textile reinforced mortar - Cao, Minh-Quyen; Nguyen, Xuan-Huy (Vietnam Journal of Mechanics, 2022)
This paper proposed an analytical model to predict the confined concrete compressive strength with textile reinforced mortar (TRM). Based on 341 compression tests, different parameters have been analyzed to clarify their influence on the compressive strength of concrete column confined with TRM. The various existing models for compressed concrete columns conﬁned by TRM have been assessed. Then, a simplified model for concrete elements wrapped with TRM are developed and verified through a best-fit analysis of the experimental database. It found that the proposed model showed good agreement with experimental results.